A new species of Caloctenus (Araneae: Ctenidae) from Colombia - Hazzi, Nicolas A.; Davila, Diana Silva (Zootaxa, 2012)
The genus Caloctenus Keyserling, 1877 comprises four species of small (3–7 mm) ground-dwelling spiders found in cloud forests and adjacent habitats of the northern Andes of South America, at elevations between 1800 to 2600 m (Silva 2004). All species apparently have a restricted geographic range and most are only known from the type locality. These spiders exhibit a cryptic coloration having a dark brown body with iridescent scales, sparse white plumose hairs and club-shaped red hairs, an ornamentation pattern that makes them indistinguishable from the leaf litter and hard to find. Recent attempts to find more caloctenine spiders in a Peruvian type locality were unsuccessful and it appears their populations, in general, are declining as fast as are their mossy and humid microhabitats.